Peculiarities of reproduction of pests of winter wheat under resource-saving fertilizer application systems in the Forest-Steppe of Ukraine - Сахненко, В. В.; Сахненко, Д. В. (Scientific Progress & Innovations, 2018)
The article generalizes the features of the formation of pest numbers when using mixtures of fertilizers and plant protection products on winter wheat crops. The specified biology, distribution, development, ecological and economic importance of pests in technologies of growing grain crops and recommended measures for the optimal use of preventive and special protective measures against pests in short-rotation field crop rotations. The regularities of the formation of enotmocomplexes in the modern application of liquid forms of fertilizers, in particular the carbamide-ammonium mixture of CAS and plant protection products, are theoretically substantiated and experimentally confirmed. The use of modern liquid forms of fertilizers KAS, 32 % and plant protection products for the cultivation of winter wheat and other cereals in the Forest-Steppe of Ukraine remains at a relatively low level: imperfection of technology, adverse climatic conditions, various stresses do not allow realizing the potential of crop productivity. The rationale for the effectiveness of such mixtures for breeding and the number of pests in modern technologies for growing crops deserves special attention in terms of optimizing the phytosanitary state of grain crops in the Forest-Steppe of Ukraine. It has been established that the best conditions for the formation of the winter wheat seed crop are created by applying fertilizers at a dose of H90 P40 and integrated plant protection. With high soil moisture and protection of plants from the pest complex, the tank mixtures are crushed, including at low moisture reserves and without plant protection, single and fragmented application of mineral fertilizers provide practically the same yield of winter wheat seeds. The relevance of the topic is due to the need to improve the effectiveness of plant protection products in mixtures of rare forms of fertilizers with the determination of their effect on the dynamics of numbers and reproduction of pests of grain crops in modern crop rotation of the Forest-Steppe of Ukraine.